2001
DOI: 10.1002/1521-3757(20010618)113:12<2359::aid-ange2359>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Terminale Borylenkomplexe als Quelle für das Borylen B−N(SiMe3)2: alternative Synthese und Struktur von [(OC)5Cr=B=N(SiMe3)2]

Abstract: Nach Bestrahlung von [(OC)5W=B=N(SiMe3)2] in Gegenwart von [Cr(CO)6] oder [CpRe(CO)3] wurden die Komplexe 1 bzw. 2 durch Intermetall‐Transfer von BN(SiMe3)2 erhalten. Damit erweisen sich terminale Borylenkomplexe als potentielle Borylenquelle bei tiefen Temperaturen und in kondensierter Phase. Verbindung 1 ist der erste strukturell charakterisierte Chromkomplex des Bors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
11

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 27 publications
(24 reference statements)
1
14
0
11
Order By: Relevance
“…Compound 2 therefore represents only the second structurally characterized cationic terminal borylene complex,6 and the first such system featuring a heteroatom donor at boron. As such, it provides a unique basis for discussion of structure and bonding, both as a function of net charge (compare with the neutral analogues [L n M(BNR 2 )])3a,b,d and borylene substituent (compare with [Cp*Fe(CO) 2 (BC 6 H 2 Me 3 ‐2,4,6)] + ) 6. As a further aid to understanding the bonding situation in 2 we have also synthesized and structurally characterized the 4‐picoline adduct [CpFe(CO) 2 {B(NCy 2 )(4‐pic)}][BAr F 4 ] − ( 4 ) (see the http://www.wiley-vch.de/contents/jc_2002/2006/z602162_s.pdf for details), thus allowing for the first time direct structural comparison of otherwise identical two‐coordinate and base‐stabilized borylenes.…”
Section: Methodsmentioning
confidence: 99%
“…Compound 2 therefore represents only the second structurally characterized cationic terminal borylene complex,6 and the first such system featuring a heteroatom donor at boron. As such, it provides a unique basis for discussion of structure and bonding, both as a function of net charge (compare with the neutral analogues [L n M(BNR 2 )])3a,b,d and borylene substituent (compare with [Cp*Fe(CO) 2 (BC 6 H 2 Me 3 ‐2,4,6)] + ) 6. As a further aid to understanding the bonding situation in 2 we have also synthesized and structurally characterized the 4‐picoline adduct [CpFe(CO) 2 {B(NCy 2 )(4‐pic)}][BAr F 4 ] − ( 4 ) (see the http://www.wiley-vch.de/contents/jc_2002/2006/z602162_s.pdf for details), thus allowing for the first time direct structural comparison of otherwise identical two‐coordinate and base‐stabilized borylenes.…”
Section: Methodsmentioning
confidence: 99%
“…In solution, the most characteristic feature of the terminal borylene complexes 77 and 78 is a 11 B NMR resonance signal at δ =92 and 87 ppm, respectively, which is considerably low‐field‐shifted with respect to that of aminoboryl compounds. In the solid state, the structural data for 77 and 78 reveal the presence of a nearly linear M‐B‐N moiety (M=Cr: 177.4(4)°,56 M=W: 177.9(5)°),55 with short BN ( 77 : 1.353(6) Å; 78 : 1.338(8) Å) and MB bond lengths (M=Cr: 1.996(6) Å, M=W: 2.151(7) Å). Curiously, all attempts at obtaining corresponding complexes [(OC) n M(BNR 2 )] from other aminoboranes X 2 BNR 2 were not successful.…”
Section: Borylene Complexesmentioning
confidence: 99%
“…Remarkably, it was found that 77 and 78 are able to transfer the aminoborylene moiety {BN(SiMe 3 ) 2 } upon photolysis to suitable borylene acceptors. Hence, photolysis of the tungsten compound 78 in the presence of [(OC) 5 Cr(NMe 3 )] effected the metal‐to‐metal borylene transfer to form chromium complex 77 56. The analogous procedure was performed in the presence of the vanadium precursor [(η 5 ‐C 5 H 5 )V(CO) 4 ] (Scheme ) or the rhenium complex [(η 5 ‐C 5 H 5 )Re(CO) 3 ] and led to the generation of the new terminal and bridging borylene species [(η 5 ‐C 5 H 5 )(CO) 3 VBN(SiMe 3 ) 2 ] ( 84 )61 and [{μ‐BN(SiMe 3 ) 2 }{(η 5 ‐C 5 H 5 )Re(CO) 2 } 2 ] ( 85 ), respectively 56…”
Section: Borylene Complexesmentioning
confidence: 99%
“…Ab initio calculations on the parent compound II and its constitutional isomer aminoborirene III have been carried out9 suggesting that II is 12.9 kcal mol −1 higher in energy than III , which is surprising given the borirene’s 2 π‐electron aromatic stabilization 10. Ever since a facile synthetic route to Group 6 terminal borylene complexes was developed,11 they have proven excellent sources for the borylene fragment 12. This borylene transfer method has developed quickly in the past decade and has been applied to the synthesis of borirenes,13 new transition‐metal borylene complexes,12, 14 metathesis reactions,15 and the insertion of the :BR fragment into olefinic CH bonds 16…”
Section: Methodsmentioning
confidence: 99%